Solid State Physics Principles and Modern Applications - Quinn, John J.; Yi, Kyung-Soo.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
Intended for a two semester advanced undergraduate or graduate course in Solid State Physics, this treatment offers modern coverage of the theory and related experiments, including the group theoretical approach to band structures, Moessbauer recoil free fraction, semi-classical electron theory, magnetoconductivity, electron self-energy and Landau theory of Fermi liquid, and both quantum and fractional quantum Hall effects. Integrated throughout are developments from the newest semiconductor devices, e.g. space charge layers, quantum wells and superlattices. The first half includes all material usually covered in the introductory course, but in greater depth than most introductory textbooks. The second half includes most of the important developments in solid-state researches of the past half century, addressing e.g. optical and electronic properties such as collective bulk and surface modes and spectral function of a quasiparticle, which is a basic concept for understanding LEED intensities, X ray fine structure spectroscopy and photoemission. So both the fundamental principles and most recent advances in solid state physics are explained in a class-tested tutorial style, with end-of-chapter exercises for review and reinforcement of key concepts and calculations.
Basic Concepts in Solid State Physics -- Crystal Structures -- Lattice Vibrations -- Free Electron Theory of Metals -- Elements of Band Theory -- Use of Elementary Group Theory in Calculating Band Structure -- More Band Theory and the Semiclassical Approximation -- Semiconductors -- Dielectric Properties of Solids -- Magnetism in Solids -- Advanced Topics in Solid State Physics -- Magnetic Ordering and Spin Waves -- Many Body Interactions #x2013; Introduction -- Many Body Interactions: Green#x2019;s Function Method -- Semiclassical Theory of Electrons -- Electrodynamics of Metals -- Superconductivity -- The Fractional Quantum Hall Effect: The Paradigm for Strongly Interacting Systems.
Keywords: Physics; Quantum physics; Optics; Electrodynamics; Condensed matter; Engineering; Optical materials; Electronic materials; Physics; Condensed Matter Physics; Optical and Electronic Materials; Engineering, general; Quantum Physics; Optics and Electrodynamics; Electronic books